Does the inspiratory muscle warm-up have an acute effect on wrestling recovery performance? - Erkan Demirkan; Mehmet Ismail Tosun; Abdurrahim Kaplan; Irem Eker Arici; Halit Harmanci; Michael Favre; Damian George Cosmin; Veysi Aslan (PLoS ONE)
This study aims to investigate the acute effects of inspiratory muscle warm-up (IMW) in young wrestlers. Wrestling is a high-intensity sport that demands anaerobic metabolism, with rapid recovery and endurance playing crucial roles in subsequent performance. Inspiratory muscle warm-up specifically targets the inspiratory muscles, reducing fatigue during exercise and helping to sustain performance. Our study compares three different warm-up protocols (traditional wrestling warm-up, wrestling warm-up (WWIW) +  IMW, and wrestling warm-up +  placebo (WWPL)) to analyse changes in inspiratory muscle strength and select respiratory function parameters. The study was conducted with 14 male wrestlers aged 15-16. Participants were subjected to the three different warm-up protocols, followed by simulated wrestling bouts. Results showed that the WWIW protocol increased maximal inspiratory pressure by 17.3% compared to the traditional and placebo warm-ups. Additionally, the WWIW protocol delayed fatigue and improved recovery rates among the wrestlers. Specifically, WWIW enabled a faster return to normal heart rate post-competition, accelerating the recovery process. These findings suggest that WWIW can be effectively used in high-intensity sports like wrestling to enhance recovery between matches and improve overall performance. Further studies with larger sample sizes and in different sports are recommended to validate these results.